Economics and culture - Throsby, C. D. (Cambridge University Press, 2001)
Brings together two very disparate areas, considering both the economic aspects of cultural activity, and the cultural context of economics and economic behaviour. The author discusses how cultural goods are valued in both economic and cultural terms, and introduces the concepts of cultural capital and sustainability.